The Dynamic Electoral Returns of a Large Antipoverty Program - Zimmermann, Laura (The Review of Economics and Statistics, 2021)
Governments around the world use short-term reelection strategies. This is problematic if governments can maximize their reelection chances by prioritizing short-term spending before an election over long-term reforms. This paper tests whether longer program exposure has a causal effect on election outcomes in the context of a large antipoverty program in India. Using a regression-discontinuity framework, the results show that length of program exposure lowers electoral support for the government. The paper discusses a couple of potential explanations, finding that the most plausible mechanism is that voters hold the government accountable for the program's implementation quality.